2016
DOI: 10.1088/1742-6596/710/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Catalytic Properties of Perovskite LaFeO3Nanoparticles

Abstract: Abstract. Orthorhombic structure of rare earth perovskite-type oxide LaFeO 3 nanoparticles with light absorption properties in the visible range was prepared by co-precipitation method. The prepared nanoparticles was characterized by several measurements such as X-ray diffraction, energy dispersive X-ray, field emission scanning electron microscope, diffuse reflectance spectroscopy, vibrating sample magnetometer and electron spin resonance spectroscopy. Methylene blue was taken as the model pollutant to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Moreover, LFO are known to show multiferroic behaviour that is the co-existence of both ferroelectric and ferro/ferri-magnetic or antiferromagnetic properties. [4] Different methodologies are there in the literature to synthesize LFO NPs like co-precipitation method, [5] solution autocombustion method, [6] sonochemical method, [7] sol-gel technique, [8] hydrothermal method, [9] Reverse Microemulsion method, [10] polymerizable complex method, [11] thermal decomposition, [12] solid-state reaction [13] and many more. Among these, the solution autocombustion method offers lots of advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, LFO are known to show multiferroic behaviour that is the co-existence of both ferroelectric and ferro/ferri-magnetic or antiferromagnetic properties. [4] Different methodologies are there in the literature to synthesize LFO NPs like co-precipitation method, [5] solution autocombustion method, [6] sonochemical method, [7] sol-gel technique, [8] hydrothermal method, [9] Reverse Microemulsion method, [10] polymerizable complex method, [11] thermal decomposition, [12] solid-state reaction [13] and many more. Among these, the solution autocombustion method offers lots of advantages.…”
Section: Introductionmentioning
confidence: 99%
“…LaCl3.7H2O (Merck), FeCl2.4H2O (Merck), and NaOH (Merck) were used to synthesize LaFeO3 nanoparticle based on our previous work [10]. Nanographene Platelets (Angstron Materials) and Graphene (Angstron Materials) with different specific surface areas of 30 m 2 /g and 400 m 2 /g were used to synthesize the composites which were labeled with LaFeO3/SA-1 and LaFeO3/SA-2, respectively.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…14 The sonication methods are promising alternatives to conventional methods due to its decreased time and energy requirements. 15 However, the utilization of complex and energy-intensive reagents in mainstream synthesis methods have influenced researchers in the direction of "green synthesis". Plant extracts have been successfully used as reducing agent or stabilizing agents in this process.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, vapor phase methods of LFO bulk synthesis were reported that utilize spray–flame pyrolysis . The sonication methods are promising alternatives to conventional methods due to its decreased time and energy requirements . However, the utilization of complex and energy-intensive reagents in mainstream synthesis methods have influenced researchers in the direction of “green synthesis”.…”
Section: Introductionmentioning
confidence: 99%